2019
DOI: 10.1186/s12906-019-2629-y
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-viral activity of culinary and medicinal mushroom extracts against dengue virus serotype 2: an in-vitro study

Abstract: Background Dengue is a mosquito-borne viral infection that has become a major public health concern worldwide. Presently, there is no specific vaccine or treatment available for dengue viral infection. Methods Lignosus rhinocerotis, Pleurotus giganteus, Hericium erinaceus, Schizophyllum commune and Ganoderma lucidium were selected for evaluation of their in-vitro anti-dengue virus serotype 2 (DENV-2) activities. Hot aqueous extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Hericium erinaceus, Schizophyllum commune, and Ganoderma lucidium were selected for evaluation of their in-vitro anti-dengue virus serotype 2 (DENV-2) activities, which were found to be more productive. Hot aqueous extracts (HAEs), ethanol extracts (EEs), hexane soluble extracts (HSEs), ethyl acetate soluble extracts (ESEs), and aqueous soluble extracts (ASEs) were prepared from the selected mushrooms to calculate the effectiveness (Ellan. et al, 2019).…”
Section: Review and Discussionmentioning
confidence: 99%
“…Hericium erinaceus, Schizophyllum commune, and Ganoderma lucidium were selected for evaluation of their in-vitro anti-dengue virus serotype 2 (DENV-2) activities, which were found to be more productive. Hot aqueous extracts (HAEs), ethanol extracts (EEs), hexane soluble extracts (HSEs), ethyl acetate soluble extracts (ESEs), and aqueous soluble extracts (ASEs) were prepared from the selected mushrooms to calculate the effectiveness (Ellan. et al, 2019).…”
Section: Review and Discussionmentioning
confidence: 99%
“…The mycelial protein fractions of L. rhinocerotis were previously reported to inhibit human papilloma virus (HPV) activity (Abdullah et al, 2010 ). The anti-dengue activity tested by plaque reduction assay against dengue virus type-2 (DENV-2) strain was detected in hot aqueous extract of L. rhinocerotis at IC 50 of 520 μg/mL (Ellan et al, 2013 ). Hot aqueous extract of L. rhinocerotis also inhibited dengue viral RNA synthesis by 99.68%.…”
Section: Description Of L Rhinocerotismentioning
confidence: 99%
“…Many people are interested in edible mushroom fruiting bodies and their mycelia as functional foods because they are less toxic and contain bioactive compounds. Investigators have reported the antitumour [14], antimutagenicity [15], antiviral [16], and antioxidant activities [17] of mushroom fruiting bodies and mycelia. Mushroom mycelia have been investigated for their potential food applications, and they are used to create fermented foods like soybeans, bread, cheese, and alcoholic drinks [18].…”
Section: Introductionmentioning
confidence: 99%